Os intelectuais autoritários e o conceito de democracia na década de 1930 e 1940. - Freire Neto, Flávio Benigno de Barros (2020)
This dissertation aims to discuss the contribution of Brazilian conservative intellectuals in the construction of ideologies and political projects during the 1930- 1940s, they are: Azevedo Amaral, Almir de Andrade, Oliveira Vianna and Integralists Plínio Salgado and Miguel Reale. Through a historiographic analysis, it is intended to demystify the simplistic view constructed about these intellectuals, since the ideas they produced at the time converged to the strengthening of a nationalist, prejudiced, conservative and corporatist discourse in their structures. The ability to interpret the cultural construction of the mentalities of the proposed timeframe in this research, allows historiography to understand and visualize the influences of these thoughts in Brazilian politics, as well as their influence in the construction of the idea/concept of democracy. Bearing in mind that it permeates in the discussion of these authors over these two decades the need for a genuinely national political model, concerning the reality, tradition, and History of the country, aiming to put an end the copies of foreign models used by the State, models seen as, not efficient and not compliant with the Brazilian context.